Design of Co Nanoparticles‐Encapsulated by Boron and Nitrogen Co‐Doped Carbon Nanosheets as Highly Efficient Electrocatalyst for Oxygen Reduction Reaction - Wen‐Jun Niu; Qiao‐Qiao Sun; Ya‐Ping Wang; Bing‐Ni Gu; Ming‐Jin Liu; Jin‐Zhong He; Jiang‐Lei Chen; Chia‐Chen Chung; Wen‐Wu Liu; Yu‐Lun Chueh (Advanced Materials Interfaces, 2021)
Abstract In this paper, for the first time, a rationally designed strategy for synthesis of Co nanoparticles encapsulated by boron and nitrogen co‐doped carbon nanosheets (CNs), namely B, N‐Co/CNs, as highly efficient electrocatalyst for oxygen reduction reaction (ORR) is demonstrated. The generated Co nanoparticles not only create well‐defined heterointerfaces with high conductivity to overcome the poor ORR activity but also promote the formation of robust graphitic carbon. The co‐existence of boron and nitrogen atoms can increase the highest occupied molecular orbital energy of sp2 hybridization, activating π electrons in graphitic CNs, thereby enhancing the activity of the catalyst. The B, N‐Co/CNs exhibit a comparable half‐wave potential (E1/2 = 0.83 V) to that of commercial Pt/C catalyst (E1/2 = 0.85 V) with a larger current density for ORR. Importantly, the homemade disposable Zn‐air battery (ZAB) is able to deliver excellent performance, including a peak power density of 93.93 mW cm−2 and a specific capacity of 727.5 mAh g−1, outperforming the Pt/C catalyst. The findings highlight a new guideline for constructing B, N‐Co/CNs catalyst with a rationally designed structure toward superior property for advanced metal‐air cathode materials.